The Influence Of Workload And Work Environment On Sustainable Performance Through Affective Commitment At PT. Pelni Sorong Branch - Rizal Fatoni; Subiyanto, Didik; Tri Kusuma, Nala (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of workload and work environment on sustainable performance through affective commitment among employees of PT Pelni Sorong Branch. Using a quantitative causal design, data were collected from 45 employees through a census method and analyzed using PLS-SEM. The results indicate that workload and work environment do not directly affect sustainable performance. However, both variables positively and significantly influence affective commitment, which subsequently enhances sustainable performance. Affective commitment also mediates the relationships between workload, work environment, and sustainable performance. These findings highlight the importance of fostering employees’ emotional attachment to improve long-term organizational performance.